PERBANDINGAN EFEKTIVITAS ANTIBAKTERI EKSTRAK BAWANG PUTIH TUNGGAL DAN MAJEMUK TERHADAP Staphylococcus aureus - Dewi, Rahajeng Mutia; Sajuni, Sajuni; Ikawaty, Risma; Aditya, Dwi Martha Nur (Universitas Ciputra Surabaya, 2024)
Infectious diseases, particularly those caused by the bacterium Staphylococcus aureus, pose a serious health issue in Indonesia. Strains of this bacterium are resistant to several antibiotics, making treatment challenging. Therefore, the use of herbal medicines such as garlic, which contain antibacterial compounds, has become a popular alternative treatment. This study aims to compare the effectiveness of single bulb garlic (Allium sativum Linn) and multiple bulbs garlic (Allium sativum) extracts as antibacterials against the growth of Staphylococcus aureus. The method used was disc diffusion (Kirby-Bauer) on Mueller-Hinton agar media with the administration of single and multiple bulb garlic extracts at concentrations of 6.25%, 12.5%, 25%, 50%, and 100%. The results of the study show that the single bulb garlic extract significantly outperforms the multiple bulbs garlic extract in terms of effectiveness. The diameter of the inhibition zone at a concentration of 100% single bulb garlic extract is 24.5, while that of the multiple bulb garlic extract is 28.5. Both types of garlic are effective as antibacterials, with the optimal concentration being 100%. However, the antibacterial activity in single bulb garlic is superior to that in multiple bulbs garlic. Therefore, single bulb garlic could serve as an effective alternative treatment.